2015
DOI: 10.1111/ene.12846
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy associated with levodopa–carbidopa intestinal infusion: a long‐term prospective assessment

Abstract: Serial clinical-electrophysiological evaluations are mandatory in patients treated with LCIG, given the possible risk of subacute and chronic PNP. No clear causative factors has been recognized in the subacute forms, whilst homocysteine-mediated neurotoxicity seems to underlie the pathogenesis of chronic forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 27 publications
3
71
2
6
Order By: Relevance
“…It was predominantly axonal in nature. This proportion was much vaster than previously reported prevalences, which range from 5% to ~40% (Ceravolo et al., 2013; Jugel et al., 2013; Merola et al., 2014, 2016; Rajabally & Martey, 2011; Shahrizaila et al., 2013; Toth, Brown, Furtado, Suchowersky, & Zochodne, 2008; Toth et al., 2010). The frequency in our LCIG group was 100% (6 of 6), in the oral group 73% (8 of 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was predominantly axonal in nature. This proportion was much vaster than previously reported prevalences, which range from 5% to ~40% (Ceravolo et al., 2013; Jugel et al., 2013; Merola et al., 2014, 2016; Rajabally & Martey, 2011; Shahrizaila et al., 2013; Toth, Brown, Furtado, Suchowersky, & Zochodne, 2008; Toth et al., 2010). The frequency in our LCIG group was 100% (6 of 6), in the oral group 73% (8 of 11).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pyridoxine deficiency increases homocysteine levels, and high doses of pyridoxine have been shown to reduce homocysteine levels (Miodownik, Lerner, Vishne, Sela, & Levine, 2007). Hyperhomocysteinemia is a common finding in levodopa therapy (Antonini, Bondiolotti, Natuzzi, & Bareggi, 2010; Mancini et al., 2014; Miller et al., 2003), and has been suggested to be a cause of neuropathy via a neurotoxic effect (Merola et al., 2016; Muller, 2008; Muller et al., 2013), as it is associated with reduced sensory nerve amplitudes (Muller, Renger, & Kuhn, 2004). We cannot rule out that cobalamin and folate play a role in the genesis of neuropathy, but our data strongly indicate that pyridoxine deficiency is a major factor.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size was too small to get statistical power and also detailed information on the effects of zinc deficiency. We have not experienced cases with peripheral neuropathy, but in previous studies, it has been reported to occur as a side effect of LCIG treatment, and homocysteine level and high dose L‐dopa were correlated to chronic peripheral neuropathy (Merola et al, , ). Obviously, it is important to accumulate more number of cases in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Routine monitoring of vitamin and homocysteine levels is recommended, given the association between levodopa treatment, vitamin B6 deficiencies, homocysteine elevation, and peripheral neuropathy . Cases of symptomatic and subclinical peripheral neuropathy (more frequently the latter) have been observed among patients treated with LCIG . Clinicians should be mindful of peripheral neuropathy symptoms (e.g., paresthesia, pain, gait abnormalities) when evaluating patients receiving LCIG and should monitor them as they would individuals receiving oral levodopa treatment.…”
Section: Monitoring and Maintenancementioning
confidence: 99%